IMPLEMENTASI PROGRAM MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) DALAM PENGEMBANGAN KOMPETENSI KERJA MAHASISWA: A SYSTEMATIC LITERATURE REVIEW - Syahmiarni; Darul Ilmi (STKIP Subang, 2025)
The Merdeka Belajar-Kampus Merdeka (MBKM) policy is a strategic government initiative design to enhanced university graduates’ employability and align higher education outcomes with the rapidly changing demands of the labor market. Through eight form off-campus learning program, MBKM aims to strengthen students’ hard and soft skills while bridging the gap between academia and industry. This study systematically reviews literature published between 2020 and 2025 that discusses the implementation of MBKM in developing students’ work competencies. A Systematic Literature Review (SLR) method was applied to analyze 30 articles sourced from Google Scholar, Garuda, and SINTA databases. Thematic synthesis was used to identify five key themes: implementation forms, effectiveness on work competencies, supporting factors, implementation barriers, and ideal models for employability. The findings indicate that MBKM effectively enhances students’ employability, particularly in communication, collaboration, and problem-solving skills. Nevertheless, challenges remain in the form of inadequate infrastructure, limited lecturer readiness, and inconsistent assessment standards. This review recommends the establishment of an outcome-based evaluation system and sustained collaboration between higher education institutions and industry stakeholders.